Exploring the communication patterns of filipino families in the discussions of type 2 diabetes risk conditions and adherence to diabetes management a case study - Arienza, Rovie Ain M. (2018)
Family discussions over non-communicable diseases such as diabetes can often be difficult and at the same time for household members. In effect, both the diagnosed individual and the members of his or her family go through emotional consequences. This study explored the communication patterns and dynamics on how families start such conversations regarding diabetes among the rest of the family members. In doing so, the researcher grounded this study with the assumptions of Family Communication Pattern Theory, categorizing families into four types ? protective, consensual, laissez-faire, and pluralistic. Three families were asked to participate in the study and were duly informed to keep their identity private (and thus, exclusion of the full interview transcriptions). They were interviewed about their individual and family experiences when it came to discussions on diabetes risk conditions and adherence to diabetes management. Furthermore, a thematic analysis was conducted and revealed three main themes characterizing the diabetes discussions and how it affects the family, in general: new family roles, discussions in the family are affected, and connection within the family. These themes were related to the family?s history on diabetes, their relationship among each other, and the communication patterns these three families exhibited. The three themes were also used to identify how the families adhere to diabetes management and what barriers seem to stop them from getting treatment. Finally, the three family cases were categorized under pluralistic type of family as informed by the FCPT.